Detection of the von Hippel-Lindau hereditary cancer syndrome: determination of mutations in the VHL gene - Milatovič, Maša; Prosenc, Uršula; Novaković, Srdjan (Onkologija : Slovenian Journal of Oncology, 2012)
The Department of Molecular Diagnostics at the Institute of Oncology Ljubljana has introduced testing of mutations in the von Hippel-Lindau (VHL) suppressor gene. Mutations in this gene increase the probability for the development of cancerous diseases associated with the »von Hippel-Lindau« (VHL) syndrome and also the development of sporadic kidney cancer. Testing of hereditary mutations in patients suspected of having the VHL syndrome enables early and correct diagnosis of the disease. Presence of a mutation in the VHL gene is sufficient to confirm the diagnosis of VHL syndrome also in the absence of typical tumours. It is tested using the direct sequencing method and the MLPA multiplex ligation-dependent probe amplification) method. While sequencing allows us to detect point mutations and small deletions and insertions, the MLPA method is used to detect the presence of large deletions and insertions in the gene or a deletion of the entire gene. Timely detection of mutations in genes associated with the development of cancer is important for the carriers of mutations, as a proven mutation is a reason for an adapted clinical monitoring and/or preventive measures in mutation carriers. This results in increased possibilities for the prevention and early detection of cancer.